PERPUTARAN KAS PERPUTARAN PERSEDIAAN DAN PERPUTARAN MODAL KERJA PADA GOFFE SAMARINDA - Aura Fathasha Adzani; Elfreda Aplonia Lau; Ivana Nina Esterlin Barus (Jurnal Trial Balance, 2025)
Working capital turnover is very important for coffee shop because it affects a business's ability to survive and develop. Working capital is funds used to meet daily operational needs, such as purchasing raw materials, paying salaries and other operational costs. Working capital turnover has several important elements, including cash turnover, inventory turnover and working capital turnover. This research aims to determine and analyze cash turnover, inventory turnover and working capital turnover at Goffee Samarinda in 2023 - 2024. The theoretical basis for this research is management accounting, specifically regarding cash turnover, inventory turnover and working capital turnover. This research was conducted at Goffee Samarinda and focused on analyzing cash turnover, inventory turnover and working capital turnover. This research uses the Goffee Samarinda report for 2022 - 2024. The analytical tools used are cash turnover ratio, inventory turnover and working capital turnover. The research results show that 1) Cash turnover at Goffee Samarinda in 2024 has increased compared to 2023 because Goffee Samarinda has succeeded in increasing sales significantly, which has an impact on increasing cash turnover. 2) Inventory turnover at Goffee Samarinda in 2024 has increased compared to 2023 due to more efficient inventory management, reduction lead time thus helping Goffee to reduce the time goods are in the warehouse, which directly increases inventory turnover. 3) Working capital turnover at Goffee Samarinda in 2024 has increased compared to 2023 because Goffee has succeeded in increasing efficiency in using current assets such as cash and inventory, where Goffee's cash turnover and inventory turnover have increased so this has an impact on increasing working capital turnover.